2004
DOI: 10.1038/sj.ejcn.1601878
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional intakes of 1072 French free-living men with and without diagnosed cardiovascular risk factors

Abstract: Objective: To compare the dietary intakes of free-living people with and without previously diagnosed diet-modifiable cardiovascular risk factors (hypertension, hypercholesterolaemia and diabetes). Design: Cross-sectional survey on cardiovascular risk factors including a three-consecutive-day food record. Setting: Multicentre setting in Lille (northern France), Strasbourg (north-east) and Toulouse (south-west) areas. Subjects: A total of 1072 middle-aged men randomly selected from the general population: group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
(34 reference statements)
0
4
0
1
Order By: Relevance
“…These data are consistent with the BMI, which is within a category defined as overweight (BMI425 kg/m 2 ) in about 30% of the entire population. Our sample population shows a high percentage of caloric intake from total fats as compared to nutritional guidelines; however, it is not as high as comparable studies performed in France, Greece and Spain (Ballesteros-Pomar et al, 2000;Karamanos et al, 2002;Capita and Alonso-Calleja, 2003;Correa Leite et al, 2003;Bongard et al, 2004;Bongard et al, 2004;Tur et al, 2004). This could be explained by the high intake of monounsaturated fatty acids (as seen by the high consumption of olive oil) in our population, which could, in part, also explain the extremely low intake of PUFA (Hu et al, 2001).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…These data are consistent with the BMI, which is within a category defined as overweight (BMI425 kg/m 2 ) in about 30% of the entire population. Our sample population shows a high percentage of caloric intake from total fats as compared to nutritional guidelines; however, it is not as high as comparable studies performed in France, Greece and Spain (Ballesteros-Pomar et al, 2000;Karamanos et al, 2002;Capita and Alonso-Calleja, 2003;Correa Leite et al, 2003;Bongard et al, 2004;Bongard et al, 2004;Tur et al, 2004). This could be explained by the high intake of monounsaturated fatty acids (as seen by the high consumption of olive oil) in our population, which could, in part, also explain the extremely low intake of PUFA (Hu et al, 2001).…”
Section: Discussionmentioning
confidence: 60%
“…Finally, red wine, generally consumed during meals, is the main alcohol intake and is relatively more prevalent with respect to other alcoholic beverages. Nevertheless, it is beyond doubt that there is no individual Mediterranean diet; in fact, some recent nutritional surveys showed that dietary habits of countries bordering the Mediterranean sea vary considerably and even inside the same country relevant differences in dietary pattern exist (Ballesteros-Pomar et al, 2000;Karamanos et al, 2002;Capita and Alonso-Calleja, 2003;Correa Leite et al, 2003;Bongard et al, 2004;Tur et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Insufficient statistical power is not a likely explanation because this study had more than 99% statistical power in men and more than 95% in women to detect a 1‐kg/m 2 difference in BMI between the Thr 347 /Thr 347 and * /Ser 347 carriers. Another explanation might be the possible influence of the French diet, which is rich in fat and alcohol (13, 14). Fat intake stimulates apoA4 synthesis (15) and increases plasma apoA4 levels (16), which may confound the effect of the APOA4 polymorphism.…”
Section: Discussionmentioning
confidence: 99%
“…23 In a cross-sectional study in France, dietary habits were compared in subjects with none, one or two and three risk factors (hypertension, hypercholesterolemia and diabetes). 24 Those aware of one or more risk factors tended to have a higher BMI, lower physical activity, lower intake of carbohydrates and higher alcohol consumption after adjustment for energy intake. Our results indicate that being aware of a risk factor such as hypertension among those with elevated blood pressure is associated with a lower BMI and lower alcohol intake.…”
Section: Discussionmentioning
confidence: 99%